The Style of Abstract Art and Its Impact on Contemporary Design in Architecture - Sakina Hassan Khaif Hamad Al-Issawi (Indonesian Journal of Cultural and Community Development, 2026)
General Background: Abstract art emerged as a major transformation in modern aesthetics by shifting artistic expression from literal representation toward the exploration of line, color, space, and form as autonomous visual elements. Specific Background: In architecture, these principles have been adopted to reorganize mass, void, light, and material into compositions that communicate intellectual, symbolic, and cultural meanings beyond functional requirements. Knowledge Gap: Although abstract art is widely recognized in visual culture, its philosophical and formal contribution to contemporary architectural design, particularly in Arab and Iraqi contexts, remains insufficiently articulated. Aims: This study aims to identify how the style of abstract art is manifested in contemporary architectural design and to define its principal characteristics. Results: Using a descriptive-analytical approach and examining three architectural samples—the Sultan Qaboos Grand Mosque, the Heydar Aliyev Center, and the Mleiha Archaeological Centre—the study found that abstraction transforms architecture into an intellectual and aesthetic system characterized by geometric simplification, integration of function and beauty, symbolic use of light and color, spatial continuity, and reinterpretation of heritage through modern forms. Novelty: The study proposes a set of theoretical indicators that explain abstraction in architecture, including structural transformation, material reduction, spatial abstraction, elimination of direct reference, and visual dynamism. Implications: These findings demonstrate that abstract art provides a conceptual framework for contemporary architectural design and supports the development of culturally grounded architectural identities within a global design discourse. Highlights: • Abstract art redefines architecture as an intellectual and aesthetic system based on geometry and spatial order.• Light, color, and materials function as symbolic design elements rather than decorative additions.• Contemporary Arab architecture uses abstraction to reinterpret heritage within modern architectural language. Keywords: Abstract Art, Contemporary Architecture, Architectural Design, Geometric Abstraction, Spatial Composition